Особенности влияния высокочастотного воздействия на характер разрушения угля - Минеев, С.П. (Геотехническая механика, 2012)
Узагальнені і проаналізовані результати досліджень за оцінкою впливу ультразвукової дії на зміну властивостей і характер руйнування вугільних зразків. Розглянуті результати досліджень за оцінкою впливу ультразвукової дії на фізико-механічні і газодинамічні властивості вугільного зразка різного ступеня викидонебезпечності, газонасичення і з урахуванням зміни напруженого стану. Встановлена закономірність ефективних частот дії на вугілля залежно від розмірів дефектних структур в ньому. The results of researches are generalized and analyzed as evaluated by influence of the ultrasonic affecting change of properties and character of destruction of coal standards. The results of researches are considered as evaluated by influence of the ultrasonic affecting physical, mechanical and gas-dynamic properties of coal standard of different degree of danger of rock outbid rust, gassings and taking into account the change of the tense state. Conformity to law of effective frequencies of affecting is set coal depending on the sizes of imperfect structures in it.